2021
DOI: 10.3390/pathogens10050536
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Identification of Multidrug-Resistant Salmonella Virchow Monophasic Variant Causing Human Septic Arthritis

Abstract: The monophasic variant of Salmonella Typhimurium has emerged and increased rapidly worldwide during the past two decades. The loss of genes encoding the second-phase flagella and the acquirement of the multi-drug resistance cassette are the main genomic characteristics of the S. Typhimurium monophasic variant. In this study, two Salmonella strains were isolated from the knee effusion and feces of a 4-year-old girl who presented with a case of septic arthritis and fever, respectively. Primary serovar identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A recent study also reported that other Salmonella serovars with the deletion of the second-phage flagellin-encoding gene cassette caused severe clinical infections in humans, e.g. the S. Virchow monophasic variant [26]. Therefore, the correlation between the loss of the fljAB region in Salmonella 4, [5],12:i:-and immune evasion, bacterial survival in niche environments or hosts and virulence needs to be further evaluated in S.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also reported that other Salmonella serovars with the deletion of the second-phage flagellin-encoding gene cassette caused severe clinical infections in humans, e.g. the S. Virchow monophasic variant [26]. Therefore, the correlation between the loss of the fljAB region in Salmonella 4, [5],12:i:-and immune evasion, bacterial survival in niche environments or hosts and virulence needs to be further evaluated in S.…”
Section: Discussionmentioning
confidence: 99%
“…Septic arthritis recurred in 38% of patients treated with systemic antibiotics and/or surgical intervention, with higher rates of treatment failure among patients with MRSA-induced infection (Salgado et al, 2007). Despite antibiotic treatment, patients with septic arthritis develop sequelae such as secondary osteomyelitis, mono-articular arthritis, limb length discrepancy, or joint fusion (Vincent & Amirault, 1990;Wang et al, 2003). Numerous studies have suggested that septic arthritis recurrence may be attributable to the ability of S. aureus to penetrate eukaryotic host cells, thus limiting the efficacy of antibiotics that primarily act within the extracellular space (Alder et al, 2020;Yu et al, 2020;Cahill et al, 2021;Kwon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%